Functional and clinical results of arthroscopic forage treatment in stage 1 Kienböch's patients - Atilgan, Numan; Demiryürek, Mehmet; Çolak, Tahsin Sami; Korucu, Ismail Hakki; Saray, Ahmet; Türkmen, Faik; Özer, Mustafa; Kaçıra, Burkay Kutluhan (EXPERIMENTAL BIOMEDICAL RESEARCH, 2024)
Aim: To compare the functional and clinical results of early stage 1 Kienböch patients in whom we performed arthroscopic forage and syneviectomy. Methods: Adult patients who applied to Necmettin Erbakan University Meram Medical Faculty Orthopedics and Traumatology outpatient clinic between 01 June 2021 and 01 June 2022 were diagnosed with Kienböch stage 1 and were to be planned for arthroscopic forage treatment were included in the study. Patients who smoked, underwent other treatment protocols and received systemic steroid treatment were excluded from the study. Quick Arm Hand and Shoulder Problems (QuickDASH) questionnaire and visual analogue Pain Scale (VAS) score were applied to the patients before and at 3 months, 6 months, 9 months and 12 months after surgery. During the clinical examination, postoperative total joint range of motion (ROM) was measured and the normal side was examined. In addition, grip and pinch strength measurements were examined. Radiological criteria such as carpal height ratio, subchondral cyst and osteophyte formation were evaluated at each control. Results: 22 patients applied to our clinic and 13 of them accepted the surgical procedure. 7 of these patients were men and 6 were women. Their average age was 27.8 years. The average follow-up period of these patients was 12 months. When the patients were examined after 12 months of follow-up, it was seen that the post-surgical vas score was significantly lower than the pre-surgical vas score (p<0.001). QuickDASH score and passive wrist movements improved significantly at postoperative follow-up. Grip strength increased significantly. Lichtman staging remained the same in 85% of patients. Conclusions: In stage 1 Kienböch patients, arthroscopic forage and wrist synovectomy are performed, minimizing the functional losses of the patients and providing a rapid decrease in pain levels. As a consequence, patients return to social and business life early and with minimal loss.